The study of mass and heat transfer on shell and tube heat exchanger - Hassanal, Haris (2012)
This research is about the shell and tube heat exchanger. The study on shell and tube heat exchanger is about to find the most effective condition for the heat exchanger to transfer heat from one stream to another stream without having any contact between both streams. This research is also to make the heat exchanger life longer than the normal operating life. The study in shell and tube heat exchanger can be only complete if the fouling is taking under consideration. The study has been made on one of Terengganu Crude Oil Terminal heat exchanger. In this research, there are few fouling problems that must be solve. The theoretical operating condition will lead the heat exchanger life up to 10 years and above. But Instead of having that in reality condition, the life that was recorded show that it is less than 10 years. It was calculated by using De Wards and Milliams Equation by tacking crude oil composition as consideration. As a procedure, the researcher tried to make the erosion fouling that promoted by corrosion less as possible. The erosion and corrosion discovered normally occurred at the bend of shell and tube heat exchanger due to high velocity and high concentration of carbon dioxide. So the study determined that after changing the flow the life can be expand.